Baccalaureate nursing students' application of social-cognitive sexual counseling for cardiovascular patients: A web-based educational intervention. (September 2016) - Steinke, Elaine E.; Barnason, Susan; Mosack, Victoria; Hill, Twyla J.
Abstract: Background: A gap in knowledge and practice exists for sexual counseling of cardiovascular patients, and innovative approaches are needed to address patients' sexual quality of life. Aim: To evaluate a web-based social-cognitive intervention for evidence-based sexual counseling by baccalaureate nursing students with cardiovascular patients. Methods: A pre- post-test survey design was used: pre-test (T1), immediate post-test after intervention (T2), and at 4 to 6 weeks post-intervention (T3). Data were collected using the Survey of Sexuality Related Nursing Practices —Cardiac version (SSRNP-CV). Data were analyzed using descriptive statistics and t -tests. Results: From T1 to T2, students (N = 95) significantly increased their responsibility and confidence in sexual counseling; from T1 to T3 (N = 57), students significantly improved sexual counseling for confidence and practice subscales, total SSRNP score, and cardiac-specific subscales of sexual counseling, sexual activity, and gender. Conclusion: This study clearly demonstrated that a web-based social-cognitive sexual counseling intervention was effective in improving students' ability to provide evidence-based sexual counseling of cardiovascular patients. Highlights: A web-based educational intervention effectively promoted sexual counseling by student nurses. Students reported increased confidence and responsibility in sexual counseling. Students engaged in sexual assessment, answered patient questions, and provided information.